Drought Response Of Grain Legumes Under Irrigation Gradient .2. Plant Water Status And Canopy Temperature - Pandey, R.K.; Herrera, W. A. T.; Pendleton, J.W. (Wiley, 1984)
A great need exists in semiarid or tropical areas to include food legumes in rice (Oryza sativa L.) based cropping systems during the post monsoon or dry season. The seed of these legumes provide needed protein for the prevalent high starch diets. Mungbean (Vigna radiata L.), cowpea (Vigna unguiculata L.), soybean (Glycine max L.), and peanut (Arachis hypogeae L.) are four short‐season legumes receiving attention. The purpose of this research was to compare their drought responses on a medium‐deep Tropudalf soil by using a line‐source sprinkler irrigation system. This paper presents findings on plant water status and canopy temperature and their relationships to yield. Plant water status was determined with a pressure chamber and canopy temperature with an infrared thermometer. Plants exhibited leaf water potentials between 1300 to 1400 h of −1.20 MPa in mungbean, −1.40 MPa in cowpea, −1.41 MPa in soybean, and −0.67 MPa in peanut in the dry regimes 60 days after emergence. Seasonal leaf water potential was closely related to canopy temperature in all four legumes. Increasing water stress decreased leaf water potential and increased canopy‐air temperature differences (ΔT). The seasonal cumulative leaf water potential and ∆T during crop growth were negatively correlated with yield and may be useful for selecting crop species for drought prone areas. Peanut had a higher leaf water potential and maintained a lower canopy temperature than the other species.